Pembelajaran Berbasis Budaya dalam Meningkatkan Mutu Pendidikan di Sekolah - I Ketut Tanu (Jurnal Penjaminan Mutu, 2016)
Education means the care for the development of the students that they grow in line with their culture. In other words, any education should pay attention to the culture of the students. Today’s curriculum tends to ignore this that the students are alienated from their own culture and are feeling that they are not part of the process of the education. The time the students are appreciated is the time when the education is done properly.